EFFECT OF BREED ON FUNCTIONAL CHARACTERISTICS OF FROZEN BULL SPERMATOZOA - NAGENDRAKUMAR, S B; KATHIRESAN, D (The Indian Journal of Animal Reproduction, 2011)
Semen samples collected from Jersey cross (n=6) and Friesian cross bulls (n=6) were extended in Tris-eggyolk-citric acid diluent. The samples were split and cryopreserved in static vapor freezing and programmed freezing.A significant influence of breed was evident on the progressive motility, percentage of intact acrosome and loss ofenzyme Aspartate transaminase while a non significant influence was noticed on the hypo-osmotic swellingresponse and percentage of live spermatozoa with intact acrosome. It was evident from the present investigationthat the there is selective influence of breed on the functional characteristics of frozen thawed semen processedby routine freezing protocols and by programmed freezing.
Keywords: Bull spermatozoa; Cryopreservation; Friesian cross; Jersey cross; Programmed freezing